Strategy For Increasing Land and Building Tax in Kendari City - Rahim, Samsuddin (International Journal of Management and Education in Human Development, 2021)
This study aims to analyze the strategy adopted by the Kendari City Government to increase land and building taxes to support the increase in Kendari City's local revenue. The object of the research is the Regional Revenue Service of Kendari City. The data was collected by using literature study, interviews and observations. The research informants were 16 people who were determined purposively. Observation phenomena included internal and external aspects. Research data were analyzed using SWOT analysis. The results of the research are strategies that are carried out to increase land and building tax revenues in Kendari City by implementing aggressive strategies, in the form of: a) conducting tax determination effectively, b) attracting new taxpayers through data collection and registration, c) streamlining the role of collectors at the village level, d) Streamlining the role of the coordination team at the sub-district level, e) optimizing IT-based PBB data management, f) implementing a geographic information system for setting taxes online.